Structured education for sustainable employment: Technology enabled queueing theory applications - Bhaskar Garimella; Sandeep Shenoy; Rashmi Yogesh Pai; Rishali Shetty (Foundations of Management, 2018)
Unemployment is a serious challenge that has been rising day by day. Skill development and creation of employment opportunities are key factors to address youth unemployment. This study emphasizes on the need for job-oriented education and to link education to employment. This study derives a mathematical model and tests the same using live university hiring data and attempts to integrate the three stakeholders, employers, education providers, and the young, each of whom have a unique approach, expectation, and understanding of the paradigm. Novel methodology inclusive of empirical evidence-based integration of objective fulfillment drafted into institutional pedagogy can help increase the success rate of education to employment from an Indian context especially Indian girls and women. The study outlines specific aspects of analytical intervention in this regard and focus-es on systematic training programs exclusively for vocational and skills amelioration executed to ad-dress this multidimensional challenge by adopting easily implementable software methodologies that are more easily implementable over a wide area network or an Internet-based application engine powered by information communication technology.
Keywords: I21; O15; E24; C6; D83; 650; Sustainable Employment; Information Communication Technology; Queueing Theory Vocational Skills; Employability; Gender Studies; University Curriculum